Watering practices for livestock in Thiruvallur district of Tamil Nadu - T. SIVAKUMAR and J. RAMESH, J.A. JIMY CAROLIN, A. YASOTHA (Indian Journal of Animal Production and Management, 2019)
A field survey was carried out in Gummidipoondi block of Thiruvallur district in Tamil Nadu during the years2017-2018 among 120 farmers to assess the watering practices for livestock. The objective of this surveywas to study the water sources available, contaminating sources of water, location of water trough, type ofwaterers, method of watering, frequency of watering, quantity of water required for livestock, water bornediseases, water treatments followed, water availability and farmers’s opinion on water quality. Most ofthe farmers used the same source of water for consumption to human and livestock. The contaminationof water sources in the study area was mainly due to industrial effluents followed by, domestic sewageand agricultural waste. Water troughs were placed outside the shed by most of the farmers. Cleaning thewater trough was practiced at weekly intervals by majority of the farmers. Aluminium vessels were used bymost of the farmers for watering the livestock. Concentrates were mixed with water by most of the farmersfor feeding the livestock. Majority of the farmers watered the cattle twice a day. Water treatment was notfollowed by most of the farmers. Water was available throughout the year as reported by almost all thefarmers. However water quality monitoring has to be carried out to assess the quality of water sourcesavailable to livestock.